2015
DOI: 10.1093/abbs/gmv052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diosmetin on airway remodeling in a murine model of chronic asthma

Abstract: Bronchial asthma, one of the most common allergic diseases, is characterized by airway hyperresponsiveness (AHR), inflammation, and remodeling. The anti-oxidant flavone aglycone diosmetin ameliorates the inflammation in pancreatitis, but little is known about its impact on asthma. In this study, the effects of diosmetin on chronic asthma were investigated with an emphasis on the modulation of airway remodeling in BALB/c mice challenged with ovalbumin (OVA). It was found that diosmetin significantly relieved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Estimation of total and differential leukocyte count (DLC) in BALF was performed following previously published methods (Thompson et al, 1996;Raju et al, 2014;Ge et al, 2015;Ambhore et al, 2019a;Kalidhindi et al, 2019a). BALF was centrifuged at 2000 rpm for 5 min at 4°C and the supernatant was discarded.…”
Section: Total and Differential Leukocyte Count In Balfmentioning
confidence: 99%
“…Estimation of total and differential leukocyte count (DLC) in BALF was performed following previously published methods (Thompson et al, 1996;Raju et al, 2014;Ge et al, 2015;Ambhore et al, 2019a;Kalidhindi et al, 2019a). BALF was centrifuged at 2000 rpm for 5 min at 4°C and the supernatant was discarded.…”
Section: Total and Differential Leukocyte Count In Balfmentioning
confidence: 99%
“…Although other labeling positions along the methylene-backbone of the stearic acid are available and could be used, it is shown that 16-DSA displays the widest difference in spectral parameters (hyperfine coupling and correlation time as described upon binding to Bovine Serum Albumin (BSA)). [17,18] The vast majority of our studies (and other reports in literature) specifically study HSA and BSA in in vitro situations (mostly buffered solutions). With the exception of a few studies that used empirical spectral parameters [8,9,19,20] to analyze paramagnetic FA binding to HSA in actual blood samples, no systematic understanding of the effects, differences, possibilities and caveats for albumin studies that ensue when one exposes FA ligands to HSA (and all other proteins and small molecules contained in blood plasma) has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…These isomers have been shown to exhibit common biological effects, such as osteoporosis prevention [5]. Diosmetin is an active ingredient of some medications [6] and has been reported to display several biological properties, including anticancer effects [7,8] and antibacterial actions [9] - . Similar to diosmetin, chrysoeriol is mainly distributed in many plant products, such as parsley [10] and peanut hull [11].…”
Section: Introductionmentioning
confidence: 99%